Burkholderia Aortic Aneurysm: A Case Report and Review of the Literature - Sreelakshmi Panginikkod; Aishwarya Ramachandran; Pratyusha Bollimunta; Roshanak Habibi; Roshan Kumar Arjal; Venu Gopalakrishnan (Case Reports in Infectious Diseases)
Melioidosis is a frequently fatal infection caused by the Gram-negative bacillus Burkholderia pseudomallei endemic to Southeast Asia and Northern Australia. It is a rare imported pathogen in the United States and is a potential bioterror agent. We report the case of an 82-year-old previously healthy man who presented with 2 weeks of fever and epigastric pain after he returned from the Philippines. A diagnosis of nondissecting mycotic aneurysm in the descending thoracic aorta was made with the help of CT angiogram and positive blood cultures. The patient completely recovered with a 6-month antibiotic therapy followed by surgical repair of the aneurysm. Given the slight increase in the number of melioidosis cases reported by CDC since 2008, melioidosis might be considered an emerging infectious disease in the United States. The purpose of this report is to raise awareness of the disease among clinicians as well as travelers.